Targeting PDK1 for Chemosensitization of Cancer Cells. - Emmanouilidi, A.; Falasca, Marco (MDPI AG, 2017)
Despite the rapid development in the field of oncology, cancer remains the second cause of mortality worldwide, with the number of new cases expected to more than double in the coming years. Chemotherapy is widely used to decelerate or stop tumour development in combination with surgery or radiation therapy when appropriate, and in many cases this improves the symptomatology of the disease. Unfortunately though, chemotherapy is not applicable to all patients and even when it is, there are many cases where a successful initial treatment period is followed by chemotherapeutic drug resistance. This is caused by a number of reasons, ranging from the genetic background of the patient (innate resistance) to the formation of tumour-initiating cells (acquired resistance). In this review, we discuss the potential role of PDK1 in the development of chemoresistance in different types of malignancy, and the design and application of potent inhibitors which can promote chemosensitization.